Answer :

Given,

⇒ 6x^{2} + 5x – 6 = 0

By splitting the middle term,

⇒ 6x^{2} + 9x - 4x – 6 = 0

Taking common in the expression,

⇒ 3x (2x + 3) – 2 (2x + 3) = 0

⇒ (2x + 3) (3x - 2) = 0

**∴** 2x + 3 = 0 and **∴** 3x – 2 = 0

**∴** and **∴**

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Introduction to Linear Equations in Two Variables62 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

The sum of two nuKC Sinha - Mathematics

Divide 12 into twKC Sinha - Mathematics

The sum of the sqKC Sinha - Mathematics

The differeKC Sinha - Mathematics

The difference ofKC Sinha - Mathematics

The sum of a numbKC Sinha - Mathematics

The difference ofKC Sinha - Mathematics

Divide 12 into twKC Sinha - Mathematics

Two numbers diffeKC Sinha - Mathematics